The Falklands War - Eddy, Paul ; Linklater, Magnus and Gillman, Peter (London Sphere Books Limited, 1984)
A detailed, workmanlike review of the 1982 War in the Falklands between Great Britain and Argentina based on extensive interviews with residents and participants in the negotiations, conflict and surrender. Considering that this was an instant history written by British authors for a home market efforts to fairly represent the Argentine side of the matter is impressive. Indeed, as regards the legalities, the authors tend to favor the Argentine side of the argument, the problem being that the current residents overwhelmingly wish to remain British.
Include Maps, Illustrations and Index.
written and edited by: Paul Eddy and Magnus Linklater with Peter Gillman ; the Insight Team: John Ball, Michael Bilton, Robin Morgan ; with the British task force: John Shirley ; In Argentina: Isabel Hilton ; Defence Correspondent: Jon Connell ; contributors: Ian Jack, Simon Winchester ; Additional reporting: Will Ellsworth Jones [and others] ; researchers: Lee Chester and Therese Stanton ; graphics: Gordon Beckett [and others] ; picture design, David Gibbons.
Keywords: Falkland Islands War (1982) -- Great Britain -- Argentina -- Diplomatic relations -- Falkland Islands